OPTIMIZATION OF MOORE FINITE STATE MACHINE IMPLEMENTED ON THE PROGRAMMABLE LOGIC - Barkalov, A.A.; Malcheva, R.V.; Soldatov, K.A. (Radio Electronics, Computer Science, Control, 2012)
This article is proposed a method which is designed to reduce the number of input variables and intermediate terms of Boolean functions. The method is based on the extended codes of states and replacement of logic conditions. Application of the proposed method allows up to 20% reduction in the total count of macrocells in blocks BLC and BFM.